Oroxylin A attenuates osteoarthritis progression by dual inhibition of cell inflammation and hypertrophy. Issue 1 (10th December 2020) - Chen, De-Heng; Zheng, Gang; Zhong, Xin-Yang; Lin, Zi-Hao; Yang, Shi-Wei; Liu, Hai-Xiao; Shang, Ping
Abstract : Oroxylin A is a promising agent to prevent osteoarthritis development by targeting cell inflammation and hypertrophy. Abstract : The imbalance between the anabolism and catabolism of the extracellular matrix (ECM) is of great importance to osteoarthritis (OA) development. Aberrant inflammatory responses and hypertrophic changes of chondrocytes are the main contributors to these metabolic disorders. In the present study, we found that Oroxylin A (ORA), a flavonoid compound derived from Oroxylum indicum, maintained ECM hemostasis of chondrocytes by Interleukin-1β (IL-1β) stimulation. Besides, it was demonstrated that IL-1β induced over-production of inflammatory mediators was attenuated by ORA treatment. Moreover, ORA could rescue IL-1β mediated hypertrophic alterations of chondrocytes. Mechanistically, ORA's protective effects were found to be associated with both NF-κB and Wnt/β-catenin signaling inhibition. Meanwhile, molecular docking analysis revealed that ORA could strongly bind to the inhibitor kappa B kinaseβ (IKKβ) and dishevelled, Dsh Homolog 2 (Dvl2), the upstream molecules of the NF-κB axis and β-catenin axis, respectively. In addition, ORA driven chondroprotective effects were also affirmed in a surgically induced OA mouse model. Taken together, the current study suggested that ORA might be a promising therapeutic option for the treatment of OA.